Strategies for graded motor imagery for clients with phantom limb pain and cognitive impairment. Issue 5 (25th October 2022) - Rich, Tonya L.; Marth, Lindsay A.; Brielmaier, Steven M.; Kiecker, Jessica E.; Vogsland, Rebecca J.; Macedo, Franz J.; Ferguson, John E.; Hansen, Andrew H.
Abstract : Background: Individuals with amputations often experience phantom limb pain (PLP) that can limit their participation in rehabilitation, prosthesis training, desired activities, and roles. One nonpharmacological rehabilitation intervention for PLP is graded motor imagery (GMI). There are several components to GMI, including right/left discrimination or laterality, motor imagery, sensory retraining, and mirror therapy. Successful implementation of GMI requires a range of cognitive skills, such as attention span, working memory, abstract reasoning, and planning. For individuals with PLP who concurrently display cognitive impairments, GMI protocols can be adapted using strategies derived from clinical practice. Objective(s): The purpose of this technical clinical report was to discuss the application of clinically implemented cognitive compensation techniques to GMI instruction. Study Design: Not applicable Methods: Clinical expert opinion to explore adaptations for GMI. Technique: Graded motor imagery can be an effective tool for pain treatment; however, some clients may need greater clinician support due to existing cognitive difficulties. Results: For clients to be successful, active engagement in learning about and implementing GMI techniques is necessary. Conclusions: When serving the lifetime amputation care needs of patients with cognitive deficits, we find that targeted learning strategies and accommodations can be helpful when introducing GMI concepts and skill development. Enhanced patient education techniques support client learning.